Retrospective study of allometric relationship between heart rate, electrocardiographic parameters and bodyweight in dogs - Aleixo, A. S. C. [UNESP]; Alfonso, A. [UNESP]; Fillippi, M. G. [UNESP]; Chiacchio, S. B. [UNESP]; Lourenco, M. L. G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The allometric relationship between bodyweight (BW) and heart rate (HR) has been described as inversely proportional in domestic species, but that has been refuted. The relationship between HR and electrocardiographic variables is described in literature. However, studies about the variation and influence of factors on the hemodynamic and electrocardiographic parameters in dogs are not abundant. As the metabolic rate is defined as the production and dissipation of heat by the body surface area (BSA) in m(2), it is essential to define that relationship. A retrospective study was conducted to analyze the correlation between HR, ECG parameters and BW in dogs. One thousand electrocardiographic tracings were analyzed in addition to the ECG parameters and clinical data such as gender, age and bodyweight. The determination of BSA was performed as follows: BSA (m(2)) = (10.1 x bodyweight (0.67)) X 10(-4). When the unified groups were analyzed, there was a negative but weak correlation (r= -0.14, P< 0.0001) between bodyweight and HR. There were differences between weight groups regarding electrocardiographic variables. There is no allometric relationship between BW and HR in dogs. Weight was associated with changes in ECG variables.
Keywords: body surface area; weight; allometric; electrocardiogram